Improving Irrigation in Asia Sustainable Performance of an Innovative Intervention in Nepal - Ostrom, Elinor 1933-2012 (Edward Elgar Pub., 2011)
Improving Irrigation in Asia is based on a longitudinal study over two decades on innovative intervention for sustained performance of irrigation systems. The work identifies key factors that can help explain the performance of interventions, and explicates lessons for resource management and the management of development assistance. In 1985, the Water and Energy Commission Secretariat of Nepal and the International Irrigation Management Institute developed an ingenious intervention program for nineteen irrigation systems located in the middle hills of Nepal in an attempt to overcome the preva
Keywords: Irrigation / Nepal; Irrigation / Népal; BUSINESS & ECONOMICS / Real Estate / General; Irrigation; Nepal / https://id.oclc.org/worldcat/entity/E39PBJqBrkJm4w88cg9k9Qfpfq; Bevattning / ekonomiska aspekter; Bevattning / Nepal; Electronic resource